Increasing yield and agronomic efficiency of boro rice (Oryza sativa) by fertigation with bed planting compared with conventional planting - Bhuyan, Md. Halim Mahmud; Ferdousi, Most. Razina; Iqbal, Md. Toufiq (International Journal of Agricultural and Biological Engineering, 2014)
The fertigation technique with raised bed planting for transplanted boro (winter, irrigated) rice production is a research focus nowadays. A field experiment compared two cultivation methods: the fertigation technique within raised bed planting on boro rice, and fertilizer broadcasting in the conventional planting method. Compared to conventional fertilizer broadcasting, results showed that the new fertigation technique in raised bed planting increased grain yield of transplanted boro rice by up to 17.04%. It yielded a greater number of panicles per square meter, a greater number of grains per panicle, higher 1000-grains weight, and better plant growth attributes. Sterility percentage and weed infestation were lower. Thirty six percent of irrigation water and time for application could be saved. Water use efficiency for grain and biomass production was higher. The agronomic efficiency of nitrogen (N) fertilizer was significantly higher. This study concluded that fertigation in raised bed planting for transplanted boro rice is a new approach with higher yield and higher fertilizer and water use efficiency than the existing agronomic practice in Bangladesh. Keywords: boro rice, fertigation with bed planting, de-nitrification, water use efficiency, harvest index, irrigated water management DOI: 10.3965/j.ijabe.20140705.004 Citation: Bhuyan M H M, Ferdousi M R, Iqbal M T. Increasing yield and agronomic efficiency of boro rice (Oryza sativa) by fertigation with bed planting compared with conventional planting. Int J Agric & Biol Eng, 2014; 7(5): 34－47.